1987
DOI: 10.1107/s0108270187092989
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the solid solution [N(CH3)4]2ZnCl1.8Br2.2 in the high- and in a new low-temperature phase

Abstract: Domains were encountered in the crystal and a large decrease of the temperature factor was observed. The phases studied are separated by two other phases: an incommensurate one and a monoclinic one with a threefold unit cell (Z = 12). The ZnHal 4 tetrahedra drive the transitions, rotating principally around the a axis (11 °) and shifting their centre along the b axis (0.42/~). Their small distortion is probably due to the crystal field effect (Hal-Zn-Hal angles range from 108.7 to 112.2°). The mean bond length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
0
11
1
Order By: Relevance
“…At T i a phase transition into an incommensurate phase occurs. From our birefringence measurements we find the value T i ϭ294 K, which differs from the value T i ϭ290 K given by Colla et al 2 The behavior of the modulation parameter ␥ in the incommensurate phase has been investigated by Vogels et al 14,15 It was found that the modulation wave vector q ជ locks at several commensurate values of ␥ in the incommensurate phases of ((CH 3 ) 4 N) 2 ZnCl 4Ϫx Br x crystals (xϾ0). The exact temperature behavior of ␥ can, however, differ from one crystal to another.…”
Section: Introductioncontrasting
confidence: 55%
See 4 more Smart Citations
“…At T i a phase transition into an incommensurate phase occurs. From our birefringence measurements we find the value T i ϭ294 K, which differs from the value T i ϭ290 K given by Colla et al 2 The behavior of the modulation parameter ␥ in the incommensurate phase has been investigated by Vogels et al 14,15 It was found that the modulation wave vector q ជ locks at several commensurate values of ␥ in the incommensurate phases of ((CH 3 ) 4 N) 2 ZnCl 4Ϫx Br x crystals (xϾ0). The exact temperature behavior of ␥ can, however, differ from one crystal to another.…”
Section: Introductioncontrasting
confidence: 55%
“…3 Thus, if one takes the difference between Cl and Br into account, all lattice translational symmetry and point group symmetry are generally lost already in the high-temperature phase. Although this has only subtle effects on x-ray diffraction experiments, 2 we show in this paper that it has definite consequences for the optical properties of these crystals.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations